The Efficacy of Ramucirumab in the Treatment of Gastric or Gastroesophageal Junction Cancer: A Meta-Analysis of RCTs - Hongqiong Yang; Yaojun Zhou; Liangzhi Wang; Tianyi Gu; Mengjia Lv; Jinling Sun; Chao Tu; Junbo He (Gastroenterology Research and Practice)
Five electronic databases were searched for eligible records. Outcomes were presented and analyzed according to the objective response rate (ORR), progression-free survival (PFS) rate, and overall survival (OS) rate. Five records involving 2,024 participants were included in the study. The pooled analysis of OS and PFS were longer with ramucirumab (RAM) therapy than without RAM for OS (odds ratio OR=0.90, 95% confidence interval CI=0.82–1.00, p=0.05) and PFS (OR=0.74, 95%CI=0.57–0.96, p=0.02). Moreover, compared with the current first-line chemotherapy, the OS (OR=0.93, 95%CI=0.83–1.04, p=0.19) and PFS (OR=0.82, 95%CI=0.64–1.06, p=0.13) results were not significantly higher with RAM. The ORRs of the patients in the RAM therapy groups were significantly higher than those in the groups without RAM (OR=1.40, 95%CI=1.14–1.73, p=0.001).